Digital design and computer architecture / David Money Harris, Sarah L. Harris. - Harris, David Money; Harris, Sarah L. (Elsevier, 2013)
'Digital Design and Computer Architecture' begins with a modern approach by rigorously covering the fundamentals of digital logic design using a hardware design language (HDL).